2022
DOI: 10.1177/15248380221120835
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dissociation and Complex Post-Traumatic Stress Disorder: A Scoping Review

Abstract: Complex post-traumatic stress disorder (CPTSD) has recently been recognized as an official psychiatric diagnosis in ICD-11, after years of research and advocacy in the field. It has been suggested that dissociative symptoms are a major feature of CPTSD. This scoping review aimed to summarize the existing knowledge base on the relationship between dissociation and CPTSD, and to identify relevant research gaps. We searched the two largest and most widely used academic databases (i.e., the Web of Science and Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…Although our hypothesis that dissociative symptoms would predict depressive symptoms was not supported by our data, we did find that dissociative symptoms were associated with PTSD and DSO symptoms, as well as poor social and occupational participation in the community. These results are consistent with the notion that dissociation may be a crucial factor leading to post-traumatic psychopathology (Fung, Chien, Lam, et al, 2022b ; Van der Hart et al, 2006 ) and is also a disabling set of symptoms that requires greater public health attention (Loewenstein, 2018 ). These results highlight the importance of early identification and management of dissociative symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although our hypothesis that dissociative symptoms would predict depressive symptoms was not supported by our data, we did find that dissociative symptoms were associated with PTSD and DSO symptoms, as well as poor social and occupational participation in the community. These results are consistent with the notion that dissociation may be a crucial factor leading to post-traumatic psychopathology (Fung, Chien, Lam, et al, 2022b ; Van der Hart et al, 2006 ) and is also a disabling set of symptoms that requires greater public health attention (Loewenstein, 2018 ). These results highlight the importance of early identification and management of dissociative symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Dissociative symptoms, which reflect disruptions in the integration of thoughts, feelings, and experiences into consciousness, might engender or worsen a variety of trauma-related symptoms, such as intrusions, affective dysregulation, and relationship difficulties. Thus, our findings highlight the potentially important role of dissociation in post-traumatic psychopathology such as complex PTSD symptoms (Fung, Chien, Lam, et al, 2022b ; Nijenhuis, 2017 ; Van der Hart et al, 2006 ).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…cPTSD often leads to dissociation, a mental mechanism that can be employed adaptively or maladaptively in response to distressing life experiences [ 67 ]. Studies indicate that among individuals with minimal exposure to trauma, dissociation may serve as a normal and even constructive aspect of the mind, possibly linked to typical self-absorption phenomena and creative coping strategies during distressing events [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic experiences, particularly childhood abuse, should be considered in the etiology of dissociation [ 23 , 24 , 25 ]. A recent review by Fung and colleagues demonstrated that a considerable number of patients with complex post-traumatic stress disorder (cPTSD) exhibited dissociative symptoms, with a clinically relevant dissociation rate of 76.9% [ 26 ]. Dissociation often functions as a defense mechanism to protect an individual’s psychological integrity against trauma [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%